Analysis of Speech Acts in Commercials on Television - Sarah Nabilah; Intan Sari Ramdhani (CV. Rayyan Dwi Bharata, 2023)
Advertising can be interpreted as news orders (to encourage, persuade) to the public/crowded people about the goods or services offered. Advertising can also be interpreted as a notification to the public regarding goods or services sold and posted in mass media, such as newspapers, magazines and electronic media such as radio, television and the internet. The use of language used in advertisements can be studied with a pragmatic approach, especially in terms of speech acts towards advertisements for food and beverage products. The implementation of this research was divided into three stages, namely (1) the stage of providing the data used was the free engagement free listening method (SBLC), proficient method and note-taking technique, (2) the stage of data analysis of illocutionary speech acts, and (3) the stage of presenting the analysis data using informal methods